A Model of the Effect of Environmental Variables on the Presence of Otters along the Coastline of the Isle of Skye. (12th August 2013) - Yoxon, Paul
Abstract : A survey of Eurasian otters ( Lutra lutra ) along the Skye coastline revealed a variation in distribution on different coastal types. Factors like geology, width of the intertidal zone, intertidal makeup, slope of coastline, inland vegetation, and number of freshwater pools could influence otter distribution. A quantitative method based on a logistic regression model is applied to take into account three scalable and four categorical environmental variables which may or may not affect otter distribution. Otter presence or absence in 500 m coastal sections was compared with binary dependent variables and a set of independent variables on 622 coastal sites. Analysis shows that this method can be used to characterise combinations of factors to predict if otters are likely to occur on a particular coastline. Geology, height 25 m above High Water Mark (indicating slope of coastline), and number of freshwater pools all affect otter utilisation of the coastal zone. Coastlines with Torridonian and Mesozoic rocks and the Landslip area show a positive effect on otters, while all other coastlines have a negative effect. Although primarily of theoretical importance, the model could be used as a tool to locate coastlines elsewhere which are of potential conservation importance for otters.